The End of an Old Enemy: Smallpox in Clay County, Kansas, 1900-1925 - Nolan, Shannon (Kansas State University, The Chapman Center for Rural Studies, 2015)
This study analyzes the cases of smallpox in Clay County, Kansas, between the years of 1900-1925. Evidence suggests proactive prevention methods were used to limit and eventually eradicate Smallpox. Data and information is drawn from county disease records and the county newspaper, along with other sources.
Shannon Nolan, “The End of an Old Enemy: Smallpox in Clay County, Kansas, 1900-1925,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/238.
Keywords: Clay County; epidemic; World War I; Porter-Morgan Hospital; Oakhill; C.M. Burke